Adaptive tracking flight control for unmanned autonomous helicopter with full state constraints and actuator faults. (September 2022) - Yan, Kun; Wu, Qingxian
Abstract: In this study, a robust adaptive flight controller is developed to achieve anticipant trajectory tracking performance for a medium-scale unmanned autonomous helicopter (UAH) with external disturbances, actuator faults and full state constraints. The flapping dynamics of the main rotors is taken into consideration in the modeling process. The adaptive method is employed to handle the unknown bounded disturbances. A novel fault tolerant control (FTC) strategy is proposed to cope with actuator faults, which can effectively overcome the singularity problem in many adaptive estimation approaches by using projection function. Meanwhile, a suitable barrier Lyapunov function (BLF) is constructed to refrain from the violation of the state constraints. Combining with the backstepping technique, the four control inputs of the medium-scale UAH system are designed in sequence. Via the Lyapunov analysis, it is proved that all error signals in the closed-loop system converge to a small neighborhood around zero. Simulation studies are carried out to reveal the validity of the presented approach. Highlights: The flapping dynamics are introduced to embody the movement of the medium-scale UAH. A novel FTC approach is proposed to deal with the actuator faults. The singularity problem of direct adaptive estimation can be solved conveniently. The developed FTC scheme can guarantee that all state constraints are not violated.